Utilization of Canva as a Learning Poster Media at SDN Kebontunggul: Pemanfaatan Canva sebagai Media Poster Pembelajaran di SDN Kebontunggul - Hariyanti, Ayunda; Hardyanto, Shendy Dwi; Sintia , Pramesti; Asmanto, Eko (International Consortium of Education and Culture Research Studies, 2025)
General Background: The advancement of educational technology has transformed teaching and learning methods, encouraging the integration of digital tools to improve student engagement and learning outcomes. Specific Background: Canva, a graphic design application, offers user-friendly features for creating engaging visual learning materials. However, disparities in digital access and literacy limit its adoption in certain educational contexts, such as SDN Kebontunggul in Mojokerto Regency. Knowledge Gap: Despite Canva’s potential, there is limited implementation and study on its integration as a learning medium in primary schools with constrained digital resources. Aims: This study aims to optimize the use of Canva as an educational tool through a structured training program initiated by students of the Pencerahan Community Service Program (KKN-P) at Universitas Muhammadiyah Sidoarjo (UMSIDA). Results: Using a five-stage methodology—planning, problem identification, training, evaluation, and reporting—the program was implemented in two phases: an introduction to Canva features and hands-on poster-making practice. The training significantly improved students’ comprehension of Canva’s functionalities and their skills in creating educational posters. Challenges such as limited digital devices and unstable internet connectivity were noted but did not hinder the overall positive outcome. Novelty: This program represents an innovative effort to introduce and apply a modern design tool in a rural primary school setting, addressing the digital divide through direct capacity building. Implications: The initiative highlights the need for continued training and infrastructural support to facilitate the broader adoption of educational technology in under-resourced schools, contributing to improved digital literacy and creativity in learning environments. Keywords: Canva, Digital Literacy, Educational Technology, Poster Design, Primary Education Highlights: Canva training improved student poster design and digital skills. Rural school challenges include limited devices and internet access. Program promotes digital tool adoption in under-resourced schools.